Assessment of large-scale motion in turbulent boundary layer subjected to a short roughness strip (2011)
Measurements have been made in a turbulent boundary layer which is subjected to a short roughness strip, with the view to examine the influence of short roughness strip on the large scale motion. This is quantified through the analysis of autocorrelation of the fluctuating velocities in the streamwise and wall-normal downstream of a roughness strip. Also, distributions of cross correlation functions are presented. The results indicate that, reference to the smooth wall, there are noticeable changes in the distributions of autocorrelation and cross correlation functions, suggesting that the large scale motion is altered as a result of the modification of the structure near the wall in the presence of the roughness element. This change extends to significant portion of the boundary layer.